2022
DOI: 10.3390/rs14051224
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Aerosol Extinction Coefficient Using Camera Images and Application in Mass Extinction Efficiency Retrieval

Abstract: In this study, we attempted to calculate the extinction parameters of PM2.5 using images from a commercial camera. The photo pixels provided information on the characteristics of the objects (i.e., the reflectivity, transmittance, or extinction efficiency) and ambient brightness. Using the RGB values of pixels, we calculated the extinction coefficient and efficiency applied to the mass concentration of PM2.5. The calculated extinction coefficient of PM2.5 determined from the camera images had a higher correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The concentration of PM can be related to RH [39,40]. As shown in Figures 2 and 3, the increase in RH in a short time could increase the concentration of PM (which is related to the hygroscopic growth of particles), while the high humidity environment (RH > 90%) for a long time (>12 h) decreased the concentration of particulate matter (wet scavenging effect).…”
Section: Surface Meteorological Conditions and Air Pollutionmentioning
confidence: 95%
“…The concentration of PM can be related to RH [39,40]. As shown in Figures 2 and 3, the increase in RH in a short time could increase the concentration of PM (which is related to the hygroscopic growth of particles), while the high humidity environment (RH > 90%) for a long time (>12 h) decreased the concentration of particulate matter (wet scavenging effect).…”
Section: Surface Meteorological Conditions and Air Pollutionmentioning
confidence: 95%
“…Further, Kim and Noh (2021) obtained the extinction coefficients of atmospheric aerosols from camera images and reported that the estimated range was 5.0 × 10 -5 to 1.0 × 10 -3 m -1 and the optimal aerosol extinction coefficient was approx. 5.0 × 10 -4 m -1 , and Shin et al (2022) reported that the range obtained from the camera images and visibility data was 2.0 ×10 -6 to 1.1 × 10 -3 m -1 . In reference to these reports, although there are differences in the air pollution conditions of the observation patches and the observation methods used, the value of atmospheric extinction coefficient is expected to be the order of 10 -6 to 10 -3 in m -1 unit, even if there is no rainfall, due to aerosol effects.…”
Section: Validity Of Extinction Coefficient For In the Case Of No Rai...mentioning
confidence: 96%
“…Because of the importance of atmospheric aerosols to air pollution and the human health impacts caused by it, traffic and airport safety, and climate change, many studies have been conducted to grasp the characteristics of aerosols (Kim & Noh, 2021). Some of these studies have reported on the relationship between atmospheric aerosols and atmospheric extinction coefficients (Kim & Noh, 2021;Ozkaynak et al, 1985;Shin et al, 2022;Uchiyama et al, 2014;Uchiyama et al, 2018). Ozkaynak et al (1985) calculated the values of extinction coefficient from the results of visibility observation in 12 airports at large cities in the U.S. and reported that they were 4.0 × 10 -5 -7.8 × 10 -4 m -1 .…”
Section: Validity Of Extinction Coefficient For In the Case Of No Rai...mentioning
confidence: 99%